TECHNOLOGICAL COMPONENT AND ITS IMPACT ON THE SUCCESS OF SMI IN SKIN CARE PRODUCT - Nordin, Mohd Ridzuan; Kasim, Raihani; Mohd Husin , Mohd Haizal; Mohamad, Imran Syakir (2007)
This paper reports the outcome of a study on the Technological Component and Its Impact on the Success of SMI in Skin Care Product. It has been found that the skin care product produced by local entrepreneur do contain technologically advance ingredients. However it was found that the foreign products tend to have more sophisticated ingredients such as proprietary and specially formulated chemical compounds. It has also been found that the local products also lag that of the foreign product as far as the inclusion of natural ingredients are concerned. As for the approach towards highlighting the technological component, the entrepreneurs of local SMI is yet to catch up with that of foreign products. In specific this paper present the quantitative study conducted by means of questionnaire administered to working women in Melaka. The objectives of the study were to determine the consumption pattern of facial moisturiser by consumers of different demographic characteristics in Malacca, followed by identifying the most frequently used brands whether they are of local or foreign brands and finally to determine the factors influencing consumer in deciding to purchase a particular facial moisturiser. The results indicated that facial moisturiser is the second most commonly used daily facial care product after the facial cleanser. Foreign brand facial moisturiser was preferred than the local brands. The technological content of the moisturiser, in specific the facial moisturiser’s ingredient was found to be the most important factor influencing consumer’s preference to purchase a particular brand of facial moisturiser.